Chemistry - Burdge, Julia (New York, NY : McGraw-Hill LLC, 2023)
"Welcome to the exciting and dynamic world of Chemistry! My desire to create a general chemistry textbook grew out of my concern for the interests of students and faculty alike. Having taught general chemistry for many years, and having helped new teachers and future faculty develop the skills necessary to teach general chemistry, I believe I have developed a distinct perspective on the common problems and misunderstandings that students encounter while learning the fundamental concepts of chemistry-and that professors encounter while teaching them. I believe that it is possible for a textbook to address many of these issues while conveying the wonder and possibilities that chemistry offers. With this in mind, I have tried to write a text that balances the necessary fundamental concepts with engaging real-life examples and applications, while utilizing a consistent, step-by-step problem-solving approach and an innovative art and media program"--Provided by publisher
1. Chemistry: the central science -- 2. Atoms, molecules, and ions -- 3. Stoichiometry: ratios of combination -- 4. Reactions in aqueous solutions -- 5. Thermochemistry -- 6. Quantum theory and the electronic structure of atoms -- 7. Electron configuration and the periodic table -- 8. Chemical bonding I: basic concepts -- 9. Chemical bonding II: molecular geometry and bonding theories -- 10. Gases -- 11. Intermolecular forces and the physical properties of liquids and solids -- 12. Modern materials -- 13. Physical properties of solutions -- 14. Chemical kinetics -- 15. Chemical equilibrium -- 16. Acids and bases -- 17. Acid-base equilibrium and solubility equilibria -- 18. Entropy, free energy, and equilibrium -- 19. Electrochemistry -- 20. Nuclear chemistry -- 21. Environmental chemistry -- 22. Coordination chemistry -- 23. Organic chemistry -- 24. Metallurgy and the chemistry of metals (Online Only). -- 25.Nonmettaclic elements and their compounds (Online Only).
Includes appendices, glossary, and index.
Keywords: Chemistry